Desenvolvimento de uma célula triaxial para estimativa da tensão horizontal em condições edométricas - Pessoa, José Rafael Diógenes (2015)
This thesis presents the development of a triaxial cell and a proposal for methodology for estimating horizontal tension edometric condition by conducting laboratory tests on samples unsaturated compacted soil in OMC. The development of triaxial cell permits the use of voltages or controlled deformation. Moreover, the machine allows independent application increments of axial and radial stresses, thereby facilitating implementation assay in any way triaxial stresses. The proposed methodology simplifies estimate lateral tension through comparison of axial stress-strain curves of the test edométrico conventional triaxial and consolidation tests under different paths tensions with the constant relationship between the axial and radial increments. In this case, the value of K0 would be corresponding to the constant trajectory in which the triaxial test curve edométrico overlaps the curve of the test in terms of stress and axial deformations. They were tests performed with different soil types and the results were- roughly consistent with estimates from correlations empirical, thus allowing validate the proposal presented in this research. also It was studied the change of horizontal stress during the collapse flood conditions in edométricas. In these tests it was found that during the breakdown voltage can horizontal remain virtually constant or even decreasing.